Cervical necrotizing fasciitis associated with descending necrotizing mediastinitis - Gonlugur Ugur; Guclu Oguz; Karatag Ozan; Mirici Arzu; Derekoy Sefa (Multidisciplinary Respiratory Medicine, 2011)
Abstract We report a case of potentially fatal cervical necrotizing fasciitis and descending necrotizing mediastinitis due to deep neck infection in a 66-year-old male patient with no history or evidence of immunocompromising disorders. On admission, he had painful neck movements and the skin over his neck was red, hot and tender. A computerized tomography (CT) scan of his neck and chest showed evidence of air collection in soft tissues. He was treated with broad-spectrum intravenous antibiotics and early massive cervical drainage. Prompt diagnosis by CT of the neck and chest enabled an early surgical treatment of cervical necrotizing fasciitis. Although acute mediastinitis is a fatal infection involving the connective tissues that fill the interpleural spaces and surround the median thoracic organs, an extensive cervicotomy combined with appropriate antibiotics can prevent the need for mediastinal drainage.